Analisis Ithnab Dalam Surah Maryam Ayat 10 Pengakuan Nabi Zakaria AS Tentang Dirinya - Abdillah; Diana; Mafruhatus (Gudang Jurnal Multidisiplin Ilmu, 2024)
This article aims to analyze the use of ithnab (extension) in Surah Maryam verse 10. The method used is literature study with a qualitative approach. Data was collected from various sources, such as tafsir books, journal articles, and related findings. Analysis is carried out by examining the meaning of ithnab, the context of the verse, and its implications in the interpretation of the verse. The research results show that the ithnab in this verse aims to emphasize the message, emphasize the meaning, and describe the greatness of Allah SWT. The use of ithnab in this verse also has stylistic and rhetorical dimensions that enrich the interpretation and provide a deep understanding of the verse. .